Cost of Production for Fresh Grapefruit in East Florida (Indian River), 2014/15 - Ariel Singerman (EDIS)
This 4-page article presents the cost of production per acre for growing fresh grapefruit in the Indian River region during 2014/15, based on a survey of growers conducted at the Indian River Citrus League production committee meeting in March 2015. The cost estimates do not represent any individual operation; rather, their purpose is to serve as a benchmark for the industry. Typical users of these estimates include growers, consultants, property appraisers, and researchers. Written by Ariel Singerman and published by the Food and Resource Economics Department, February 2016.